Justice as an aspect of the polis idea in Solon's political poems : a reading of the fragments in light of the researches of new classical archaeology - Almeida, Joseph A. (Leiden, Netherlands ; Boston : Brill, 2003)
This book examines the meaning of justice or ""dike"" in the political poems of Solon from a new interpretative perspective. The first two chapters argue that neither standard historical nor literary treatments have provided an adequate foundation for understanding Solon's ""dike"". The main defect lies in an inability to connect Solon's concrete political work with his poetic perceptions. The book's central proposal is that the polis idea, from new classical archaeology, provides an objective standard for an interpretation of Solon's ""dike"", which remedies this defect. The third chapter set.
Law Givers and the Deros Inscription: the Polis Idea before the Hoplite -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- W.
Includes bibliographical references (pages 267-265) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Solon, -- approximately 630 B.C.-approximately 560 B.C. -- Poetic works; Solon, -- approximately 630 B.C.-approximately 560 B.C.; Solon; Political poetry, Greek -- History and criticism; Excavations (Archaeology) -- Greece -- Athens; Politics and literature -- Greece -- Athens; Athens (Greece) -- Politics and government; Justice in literature; Fouilles (Archéologie) -- Grèce -- Athènes.; Politique et littérature -- Grèce -- Athènes.; Justice dans la littérature.; Poésie politique grecque -- Histoire et critique; LITERARY CRITICISM -- Ancient & Classical; Criticism and interpretation; Excavations (Archaeology); Justice in literature; Political poetry, Greek; Politics and government; Politics and literature; Greece -- Athens; Politische Literatur; Gerechtigkeit; Polis; Griekse oudheid; Gerechtigheid; Stadstaten; Gedichten; Criticism, interpretation, etc